PNEUMOTHORAKS EC TB PARU: LAPORAN KASUS - Dewi Murni Manihuruk; Siska Andriani Rukmana (LPPM Universitas Abdurrab, 2023)
A 39-year-old male patient came to the emergency department of the hospital with complaints of shortness of breath since 4 days ago. Shortness of breath was accompanied by a cough without phlegm, right chest pain, fever, and weight loss. History of long cough and history of trauma were denied. The patient is an active smoker since Â± 17 years. Vital signs examination found blood pressure, pulse and temperature within normal limits, respiratory frequency 26 x/min, SpO2 96%. The patient's nutritional status was 15.2 (underweight). Physical examination of the thorax inspection was asymmetrical, the dextra hemithorax was left behind, on palpation there was asymmetrical tactile fremitus, percussion was hypersonic in the dextra hemithorax, and the breath sound was weakened in the dextra hemithorax. The patient underwent a supporting examination in the form of routine blood laboratory tests, BTA tests, and HIV screening as well as X-rays. The results of routine blood laboratory tests were within normal limits, TCM TB sputum examination was absent. Thoracic x-ray examination with the impression of dextra pneumothorax. The patient was diagnosed with dextra pneumothorax with pulmonary TB. The patient was fitted with a WSD, and managed with antituberculosis drugs (OAT).